Replays of Reports and Songs
Report of Saddam's letter to his nation, read by Sahhaf; report of Bedouins and Arabs supporting the leadership; report of Sahhaf press conference, where he claims the enemy is out of Saddam's airport; report claiming the enemy has been defeated at several places.